Gender differences between WOMAC index scores, health-related quality of life and physical performance in an elderly Taiwanese population with knee osteoarthritis. Issue 9 (15th September 2015) - Fang, Wen-Hui; Huang, Guo-Shu; Chang, Hsien-Feng; Chen, Ching-Yang; Kang, Chi-Yu; Wang, Chih-Chien; Lin, Chin; Yang, Jia-Hwa; Su, Wen; Kao, SenYeong; Su, Sui-Lung
Abstract : Objective: To investigate the importance of the WOMAC index score, health-related quality of life and physical performance in each domain affected by knee osteoarthritis (OA) and to identify gender differences in the importance of these domains and physical performances. Material and methods: We performed a population-based study for radiographic knee OA among participants aged more than 65 years. Demographic data were collected and anthropometric measurement, radiographic assessment, the WOMAC index score, the short-form 12 (SF-12), the Timed and Up to Go Test (TUGT) and the Five Times Sit to Stand Test (FTSST) were performed. Result: There were 901 individuals (409 males and 492 females) aged 74.04±6.92 (male: 76.35±7.33; female: 72.12±5.92) years included in this study. The WOMAC scores of participants with OA were higher than those without OA in males and females (male: 11.97±15.79 vs 8.23±12.84, p<0.001; female: 10.61±14.97 vs 7.59±3.31, p=0.032). The physical component summary (PCS) score was only significant in females with knee OA (62.14±24.66 vs 66.59±23.85, p=0.043), while the mental component summary (MCS) score was only significant in males with knee OA (78.02±18.59 vs 81.98±15.46, p=0.02). The TUGT and FTSST were not significant in individuals with and without OA in males and females. Moreover, the multivariate results for the WOMAC score were significant for females (3.928 (95% CI 1.287 to 6.569), p=0.004). Conclusions: The PCS domains of SF-12 and MCS domains of SF-12 are crucial in Taiwanese females and elderly males, respectively, with knee OA. Different evaluation and treatment strategies based on gender differences should be considered in elderly Taiwanese patients with knee OA to improve their quality of life.